Effect of forage-to-concentrate ratio on production efficiency of low-efficient high-yielding lactating cows - Y.A. Ben Meir; M. Nikbachat; Y. Portnik; S. Jacoby; G. Adin; U. Moallem; I. Halachmi; J. Miron; S.J. Mabjeesh (Animal, 2021)
Feed is usually the costliest input in lactating cow's farms. Therefore, the developing of methods for a better adjustment of feed intake to cow's energetic needs in order to improve efficiency is desired. The aim of this study was to improve feed efficiency of low-efficient (LE) cows through a moderate increase in diet forage-to-concentrate ratio. We studied the effects of replacing 8.2% corn grains in a control low-fiber (LF) diet that contained 17.5% forage neutral detergent fiber (NDF) with 7.5% wheat straw +0.7% soybean meal for a high-fiber (HF) diet that contained 23.4% forage NDF. Based on efficiency data of individual cows from the Agricultural Research Organization's herd measured in our previous study, 15 pairs of pre-classified LE multiparous mid-lactating Israeli Holstein dairy cows were selected, each pair with similar performance, intake, and efficiency data; each member of a pair was then adapted for 2 weeks to one or the other dietary treatment. Traits examined during the 5 weeks of the experiment were DM intake (DMI), eating behavior, milk production, in vivo digestibility, and estimation of feed efficiency [energy-corrected milk (ECM)/DMI and energy balance]. Cows fed the HF diet showed slower eating rate, smaller visit and meal sizes, longer daily eating time, higher visit frequency, and longer meal duration, compared to those fed the LF diet. The DMI of cows fed the HF diet was 9.1% lower, their DM digestibility decreased from 65.7 to 62.2%, and their ECM yield was 7.0% lower than in cows fed the LF diet. Feed efficiency, measured as net energy captured/digestible energy intake, improved in the cows fed the HF vs. LF diet while feed efficiency measured as ECM/DMI remained similar. Our results thus show the potential of improving feed efficiency for milk production in LE cows by increasing the forage-to-concentrate ratio.